Occupational Therapy Predischarge Home Visits in Acute Hospital Care: A Randomized Trial. Issue 10 (7th September 2016) - Clemson, Lindy; Lannin, Natasha A.; Wales, Kylie; Salkeld, Glenn; Rubenstein, Laurence; Gitlin, Laura; Barris, Sarah; Mackenzie, Lynette; Cameron, Ian D.
Abstract : Objectives: To determine whether an enhanced occupational therapy discharge planning intervention that involved pre‐ and postdischarge home visits, goal setting, and follow‐up (the HOME program) would be superior to a usual care intervention in which an occupational therapy in‐hospital consultation for planning and supporting discharge to home is provided to individuals receiving acute care. Design: Randomized controlled trial. Setting: Acute and medical wards. Participants: Individuals aged 70 and older (N = 400). Measurements: Primary outcomes: activities daily living (ADLs; Nottingham Extended Activities of Daily Living) and participation in life roles and activities (Late Life Disability Index (LLDI)). Results: Occupational therapist recommendations differed significantly between groups ( P < .001) (HOME n = 892 recommendations; control n = 329 recommendations). There was no difference between groups in ADLs (Nottingham Extended Activities of Daily Living scale (NEADL): β = −0.17, 95% confidence interval (CI) = −0.99–0.66) or participation (LLDI—Frequency: β = −0.23, 95% CI = −2.05–1.59; LLDI—Limitation: β = −0.14, 95% CI = −2.86–2.58). Both groups maintained prehospital functional status at 90 days, and there was no difference between groups in the number of people with unplanned readmissions (HOME 23.5%, n = 43; control 21.9%, n = 37). When groups were combined, being male ( P = .03) or having lower perceived participation because of physical problems ( P = .04) resulted in higher risk of unplanned readmissions. Conclusion: HOME discharge planning, which had a strong emphasis on task modification, well‐being, and prevention strategies, implemented twice as many occupational therapy recommendations as the in‐hospital only consultation, which had a greater emphasis on equipment provision, but HOME did not demonstrate greater benefit in global measures of ADLs or participation in life tasks than in‐hospital consultation alone. It is not recommended that home visits be conducted routinely as part of discharge planning for acutely hospitalized medical patients. Further work should develop guidelines for quality in‐hospital consultation.